MENTAL ILLNESSES AS VIEWED FROM THE IDEA OF PHYSICAL EXERCISE (Fiep Bulletin - online, 2014)
This study has the objective of discussing the importance of physical activity as a means of treatment of the mentally ill, thereby modifying his quality of life.  We would like to emphasize the importance of physical activity as an instrument of well being mentally and physically.  We also want to present a few historical aspects of the mental illness, related to it's significance and how it has been perceived over the years.  We want to present our plan of physical activity that the PROAMDE (Program of Motor Activities for Deficient persons) performs with those diagnosed with mental illness in a group of adults that are mentally deficient.
Keywords: Physical Activity; Mental Illness; inclusion